2018
DOI: 10.3390/separations5040054
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption and Bioaccumulation Abilities of Actinomycetes/Streptomycetes Isolated from Metal Contaminated Sites

Abstract: Heavy metal pollution is of great concern. Due to expansion of industrial activities, a large amount of metal is released into the environment, disturbing its fragile balance. Conventional methods of remediation of heavy metal-polluted soil and water are expensive and inefficient. Therefore, new techniques are needed to provide environmentally friendly and highly selective remediation. Streptomycetes, with their unique growth characteristics, ability to form spores and mycelia, and relatively rapid colonizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(62 citation statements)
references
References 58 publications
0
49
0
2
Order By: Relevance
“…to Firmicutes, Proteobacteria, and Actinobacteria phyla, are among the most widely spread and frequently listed bacterial genera in TE-contaminated soils, and at the same time display a high TE tolerance (Pires et al, 2017;Chellaiah, 2018;Chen et al, 2018;Cui et al, 2018). Nonetheless, Sphingomonas, member of the Proteobacteria (Xie et al, 2010;Chen et al, 2014;Jaafar, 2019), as well as Pseudarthrobacter (Chen et al, 2014;Fekih et al, 2018;Park et al, 2019), Nocardioides (Bagade et al, 2016;Cui et al, 2018), and Streptomyces (Álvarez et al, 2013;Cui et al, 2018;Durand et al, 2018;Lasudee et al, 2018;Timková et al, 2018;Álvarez-López et al, 2020), belonging to the Actinobacteria, were also highlighted for displaying TE-tolerance and even studied for potential remediation applications. Indeed, these bacterial genera are known to accumulate Cd, Ni, Cr or Pb from TE-contaminated soils and to induce changes in the oxidation state of the TE (Pires et al, 2017;Chellaiah, 2018;Timková et al, 2018).…”
Section: Dominance Of Actinobacteria and Proteobacteria Phyla In The mentioning
confidence: 99%
“…to Firmicutes, Proteobacteria, and Actinobacteria phyla, are among the most widely spread and frequently listed bacterial genera in TE-contaminated soils, and at the same time display a high TE tolerance (Pires et al, 2017;Chellaiah, 2018;Chen et al, 2018;Cui et al, 2018). Nonetheless, Sphingomonas, member of the Proteobacteria (Xie et al, 2010;Chen et al, 2014;Jaafar, 2019), as well as Pseudarthrobacter (Chen et al, 2014;Fekih et al, 2018;Park et al, 2019), Nocardioides (Bagade et al, 2016;Cui et al, 2018), and Streptomyces (Álvarez et al, 2013;Cui et al, 2018;Durand et al, 2018;Lasudee et al, 2018;Timková et al, 2018;Álvarez-López et al, 2020), belonging to the Actinobacteria, were also highlighted for displaying TE-tolerance and even studied for potential remediation applications. Indeed, these bacterial genera are known to accumulate Cd, Ni, Cr or Pb from TE-contaminated soils and to induce changes in the oxidation state of the TE (Pires et al, 2017;Chellaiah, 2018;Timková et al, 2018).…”
Section: Dominance Of Actinobacteria and Proteobacteria Phyla In The mentioning
confidence: 99%
“…In addition, cell wall peptidoglycans and/or surface extracellular polymers with cell wall dissociation could also form effective biosorption matrices to adsorb metal ions (Vijayaraghavan and Yun 2008). Gram-positive microorganisms had a large adsorption capacity because they have a thick peptidoglycan layer and contain a large number of adsorption sites (Timková et al 2018). François et al (2012) also confirmed that the biosorption of mercury by Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…The scarce aqueous solubility and bioavailability of Fe and its importance for several biological functions led microorganisms to evolve specific mechanisms of Fe-uptake and Fe-trapping, mostly represented by siderophore biosynthesis [ 51 , 52 ]. Siderophores are low-molecular-weight (200–2000 Da) and diffusible molecules featuring a high affinity and selectivity for the insoluble ferric (Fe 3+ ) as compared to ferrous (Fe 2+ ) cations, which guarantees a low level of competition with other bivalent yet essential metal cations(e.g., Zn 2+ , Cu 2+ , Ni 2+ , and Mn 2+ ) [ 53 ].…”
Section: Mechanism(s) Of Metal Tolerance and Resistance In Actinobmentioning
confidence: 99%
“…Siderophores are low-molecular-weight (200–2000 Da) and diffusible molecules featuring a high affinity and selectivity for the insoluble ferric (Fe 3+ ) as compared to ferrous (Fe 2+ ) cations, which guarantees a low level of competition with other bivalent yet essential metal cations(e.g., Zn 2+ , Cu 2+ , Ni 2+ , and Mn 2+ ) [ 53 ]. Thus, siderophores’ biosynthesis and secretion usually depend on Fe 3+ environmental concentration [ 52 , 53 , 54 ], as they act as Fe-chelators, creating extracellular iron-siderophore complexes from which Fe 3+ is taken up by bacterial cells through redox processes [ 53 , 55 ]. After the first study reporting the production of the siderophores arthrobactin and mycobactin by Arthrobacter terregens and Mycobacterium johnei in the 1950s [ 53 ], actinobacterial members have been described to be able to synthesize siderophores, which, depending on their chemical structure, are indicated as phenolates, catecholates, carboxylates, hydroxamates, or mixed types [ 56 , 57 , 58 ] ( Table 1 ).…”
Section: Mechanism(s) Of Metal Tolerance and Resistance In Actinobmentioning
confidence: 99%